Smoking Cessation in the ITALUNG Lung Cancer Screening: What Does "Teachable Moment" Mean?. Issue 9 (23rd August 2019) - Pistelli, Francesco; Aquilini, Ferruccio; Falaschi, Fabio; Puliti, Donella; Ocello, Cristina; Lopes Pegna, Andrea; Carozzi, Francesca Maria; Picozzi, Giulia; Zappa, Marco; Mascalchi, Mario; Paci, Eugenio; Carrozzi, Laura; et al.
Abstract: Background: Changes in smoking habits and predictors of smoking cessation were examined in the randomized ITALUNG lung cancer screening trial. Methods: In three centers, eligible smokers or ex-smokers (55–69 years, ≥20 pack-years in the last 10 years) were randomized to receive annual invitation for low-dose computed tomography for 4 years or usual care. At invitation, subjects received written information for a free smoking cessation program. Quitting outcome was assessed at year 4. Results: Among participants who completed baseline assessments and year 4 screening, higher quitting (20.8% vs. 16.7%, p = .029) and lower relapse (6.41% vs. 7.56%, p = .50) rates were observed in the active screening group as compared to the usual-care control group. Corresponding figures in the intention-to-treat analysis were as follows: 16.04% versus 14.64% ( p = .059) and 4.88% versus 6.43% ( p = .26). Quitting smoking was significantly associated to male gender, lower pack-years, and having pulmonary nodules at baseline. Center-specific analyses showed a threefold statistically significant higher probability to quit associated with participating in the smoking cessation program. A subsample of smokers of the scan group from one center showed higher quitting rates over 12-month follow-up as compared to matched controls from the general population who underwent the same smoking cessation program. Conclusions: Consistently with previous reports, in the ITALUNG trial, screened subjects showed significantly higher quit rates than controls, and higher quit rates were associated with both the presence of pulmonary nodules and participating in a smoking cessation program. Maximal effect on quitting outcome was observed with the participation in the smoking cessation program. Implications: Participating in lung cancer screening promotes smoking cessation. An effective "teachable moment" may be achieved when the smoking cessation intervention is structured as integral part of the screening clinical visits and conducted by a dedicated team of health care professionals. Standardized guidelines for smoking cessation interventions in lung cancer screening are needed.